IDENTIFIKASI SEBARAN DAN KETEBALAN LAPISAN BATUBARA BERDASARKAN DATA WELL LOGGING DI PT BORNEO EMAS HITAM LOA TEBU KALIMANTAN TIMUR - Ernia, Yuyun; Djayus, Djayus; Supriyanto, Supriyanto (GEOSAINS KUTAI BASIN, 2020)
The increase of coal demand must followed by the exploration, including distributin and thickness of coal seam. The data that has beeen used in this research was recondary data in the form of Well Logging data (Gammar Ray Log and Density Log) and coring data. Gamma Ray Log and Density Log was interpreted to obtain rock lithology, then processed by using software to obtain. Seread and thickness of coal seam, correlation between boreholes. The result are identification of seread direction, depth and thickness of coal seams bared on. Coal’s distribution analysis at research area, identified area of coal seams distribution. Relative to the southwest and north east. With four coal seams. Three seams having split or branching. Seam A with average thickness value 0,43 m, seam B with average thickness value 0,26 m and seam D with average thickness value 0,24 m. the widest seam distribution was seam A and B while the fewest seam was seam D.